1996
DOI: 10.1590/s0037-86821996000500004
|View full text |Cite
|
Sign up to set email alerts
|

Control of parasitic infections among school children in the peri-urban area of Botucatu, São Paulo, Brazil

Abstract: The prevalence of intestinal parasitosis was investigated in a primary school located in Rubião Júnior, a peri-urban district of Botucatu, São Paulo state, Brazil, in order to assess the effect of treatment and practical measures of prophylaxis in the control of parasitic infections among 7-to-18-year-old school children of a low socio-economic status. The first series of parasitological examinations included 219 school children, of which 123 (56.1%) were found to be infected with one or more parasite species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
4
0
8
Order By: Relevance
“…Segundo Fernandez (2006) em seu estudo com crianças de creches e escolas do município de Poços de Caldas-MG, a faixa etária mais afetada por protozoários encontra-se entre 2 e 10 anos. As crianças do sexo masculino apresentaram uma taxa de parasitose maior quando comparadas às crianças do sexo feminino, dado semelhante ao encontrado por Dórea et al (1996), que observaram uma maior __________________________________________________________________________________________ Editora Unijuí -Revista Contexto & Saúde, vol. 17, n. 32, 2017-ISSN 2176 prevalência de parasitoses no sexo masculino, sugerindo um maior contato com o solo em suas brincadeiras e menor frequência no uso de calçados.…”
Section: Discussionunclassified
“…Segundo Fernandez (2006) em seu estudo com crianças de creches e escolas do município de Poços de Caldas-MG, a faixa etária mais afetada por protozoários encontra-se entre 2 e 10 anos. As crianças do sexo masculino apresentaram uma taxa de parasitose maior quando comparadas às crianças do sexo feminino, dado semelhante ao encontrado por Dórea et al (1996), que observaram uma maior __________________________________________________________________________________________ Editora Unijuí -Revista Contexto & Saúde, vol. 17, n. 32, 2017-ISSN 2176 prevalência de parasitoses no sexo masculino, sugerindo um maior contato com o solo em suas brincadeiras e menor frequência no uso de calçados.…”
Section: Discussionunclassified
“…This was also observed (for hookworms) by Miranda et al 20 , among indigenous men of the Tembé ethnic group. Although some studies have suggested that men have greater contact with infecting forms that are contained in the soil, new studies relating age groups to activity and sex should be conducted to clarify this question better 11 . We can highlight the precarious sanitary conditions in which the Terena Indians live as a contributory factor towards the high general prevalence observed in the Tereré settlement.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between soil contamination and intensity of infection in the human population was not analysed. A couple of studies analysed prevalence after treatment: Dorea et al [32] performed stool examination in primary school children at 4 and 6 months after treatment with thiabendazole (with 4•1% prevalence at time 0) and found 50% prevalence reduction. Heukelback et al [15] evaluated prevalence before and after 1 and 9 months from mass treatment with ivermectin (two doses given 10 days apart), finding a reduction from 11% to 0•6% and 0•7%, respectively.…”
Section: Strongyloidiasis In the Different La Countriesmentioning
confidence: 99%